The effects of more intensive counselling for disadvantaged unemployed youth - Rainer Eppel; Helmut Mahringer (Austrian Institute of Economic Research (WIFO), 2022)
Many European countries are facing the key challenge of integrating low-skilled jobless young people into the labour market. From 2018 to 2020, the Public Employment Service (PES) in Vienna tested a new model of intensified support ("case management"). The target group consisted of young unemployed persons with low formal qualifications who were drawing on social assistance. Based on the pilot project and a propensity matching approach, we show that the increase in staff significantly increased the intensity of the counselling. It led to an increase in job proposals and active labour market programme participation, as well as sanctions in the form of benefit suspensions for failure to keep PES appointments. In line with the goal, more of the young people were encouraged to take part in training and further education instead of being quickly placed in an unskilled job. However, in the three-year follow-up period, the intensified counselling did not (yet) have a significant effect on the overall extent of integration into employment. Regarding post-unemployment job quality, we find no effects on wages at the start of a job.
Keywords: J64; J68; 330; unemployment; low-skilled youths; active labor market policy; Public Employment Service; counseling intensity; case management; Arbeitslosigkeit; gering qualifizierte Jugendliche; aktive Arbeitsmarktpolitik; Arbeitsmarktservice; Beratungsintensität